Hymenoptera parasitóides de larvas de Lepidoptera associadas a Croton floribundus Spreng (Euphorbiaceae) - Fernandes, Luciana Bueno dos Reis (Universidade Federal de São Carlos, 2003)
The Hymenoptera were collected during an inventory of wild-caught Lepidoptera larvae and their parasitoids feeding on Croton floribundus. The Lepidoptera larvae were obtained by direct search on host plants, using an entomological umbrella on shrubs and a white cloth (3,3 m2) extended on the floor under the plants, shaken by a stick, along tracks inside of three preserved forest areas in São Paulo State (Canchim Farm, CPPSE / EMBRAPA, at São Carlos; Cambuhy Farm at Matão; Anchieta Island Forest Reserve at Ubatuba). Sixty species, belonging to families Braconidae, Ichneumonidae, Chalcididae, Encyrtidae, Eulophidae, Perilampidae, Pteromalidae and Bethylidae, were reported; most of them were for the first time associated with C. floribundus. Biological data were obtained and many Lepidoptera and Hymenoptera (both immature and adults) were illustrated.
Hymenoptera parasitoids of Lepidoptera larvae associated to Croton floribundus Spreng (Euphorbiaceae)
Keywords: Hymenoptero; Lepidoptera; Interação inseto-planta; Ecologia; CIENCIAS BIOLOGICAS::PARASITOLOGIA::ENTOMOLOGIA E MALACOLOGIA DE PARASITOS E VETORES